2022
DOI: 10.1017/s0021859622000570
|View full text |Cite
|
Sign up to set email alerts
|

Composting from organic municipal solid waste: a sustainable tool for the environment and to improve grape quality

Abstract: Composting from organic municipal solid waste (MSW), such as a separate waste collection, is a valid tool for eliminating a considerable amount of waste that would otherwise be destined for landfills and incinerators, thus representing an effective complement to traditional forms of recycling. It allows organic substance to be recovered and reintegrated into the soil, thus preventing erosion phenomena, increasing the biological fertility of the soil and contributing significantly to the restoration of impoveri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 77 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…This increase in Zn value was obtained in 2% of MSWC applications; Zn value increased in 1% and 2% of MSWC applications but decreased in 4% of MSWC applications [57]. Cataldo et al [21] examined alternatives to MSWC applications at different doses (2.5, 15 and 40 tons ha −1 ) to provide sustainable crop yield and vegetative growth in vines. According to the 2019 data of Cataldo et al [21], micronutrients Fe, Zn and Cu are affected at MSWC application doses, and they reported that as the MSWC application dose increased, the Fe and Cu values also increased, and the highest values were obtained from 40 tons ha −1 of MSWC application compared to the control.…”
Section: Macro and Micronutrient Elements In Leaves Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…This increase in Zn value was obtained in 2% of MSWC applications; Zn value increased in 1% and 2% of MSWC applications but decreased in 4% of MSWC applications [57]. Cataldo et al [21] examined alternatives to MSWC applications at different doses (2.5, 15 and 40 tons ha −1 ) to provide sustainable crop yield and vegetative growth in vines. According to the 2019 data of Cataldo et al [21], micronutrients Fe, Zn and Cu are affected at MSWC application doses, and they reported that as the MSWC application dose increased, the Fe and Cu values also increased, and the highest values were obtained from 40 tons ha −1 of MSWC application compared to the control.…”
Section: Macro and Micronutrient Elements In Leaves Parametersmentioning
confidence: 99%
“…Cataldo et al [21] examined alternatives to MSWC applications at different doses (2.5, 15 and 40 tons ha −1 ) to provide sustainable crop yield and vegetative growth in vines. According to the 2019 data of Cataldo et al [21], micronutrients Fe, Zn and Cu are affected at MSWC application doses, and they reported that as the MSWC application dose increased, the Fe and Cu values also increased, and the highest values were obtained from 40 tons ha −1 of MSWC application compared to the control. In the Mn value, when compared to the control, the highest value was obtained from 15 tons ha −1 of MSWC application, according to the 2019 data of Cataldo et al [21].…”
Section: Macro and Micronutrient Elements In Leaves Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of natural organic waste materials to agricultural soils appears to be a valuable solution as a potential P source, mainly due to a sufficiently high abundance of phosphorus in the waste materials. The application of compost, formed by processing waste biomass including municipal waste, in agricultural practice is one of the particularly promising and profitable directions [5][6][7][8][9][10][11][12][13]. A particular strength of organic waste applications is that they have been shown to increase the bioavailable P content in soils [1,[14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The mineralization and transformation of organic matter in the composting of organic waste, including municipal solid waste, provides a stable product that has high fertilising potential, which can improve the chemical and physical properties of cultivated soils and, consequently, can have a positive impact on soil quality [7,[26][27][28][29][30]. During the composting process, which involves the transformation of organic matter, there are also significant transformations in the P content and proportions between different P forms, which can have a significant impact on the suitability of such material as a source of P in soil.…”
Section: Introductionmentioning
confidence: 99%